"Bridging Science and Society: The Interrelation of DNA Profiling, Criminal Investigation and Public Health" – A review - Vyas, Shivangi (South Eastern European Journal of Public Health, 2024)
DNA profiling has emerged as one of the most transformative tools in modern science, significantly impacting criminal justice and public health. Its ability to identify individuals with unparalleled precision has revolutionized investigative procedures, facilitated justice, and informed health strategies. Despite its profound benefits, DNA profiling intersects with complex ethical, legal, and philosophical questions, particularly in the realms of privacy, human rights, and the potential misuse of genetic information. The evolution of DNA profiling technology, from its early applications in forensic science to its expanded roles in disease prevention and personalized medicine, highlights its multifaceted utility. In criminal investigations, DNA profiling aids in identifying perpetrators, exonerating the innocent, and solving cold cases. However, its integration raises concerns about privacy, potential stigmatization, and the erosion of the presumption of innocence. In public health, DNA profiling offers insights into genetic predispositions and fosters advancements in precision medicine, yet it also poses challenges regarding ethical use and equity.From a theoretical perspective, DNA profiling engages with criminological frameworks such as Cesare Lombroso’s “born criminal” theory and modern understandings of sociological and environmental determinants of crime. This interplay underscores the nuanced relationship between biology and behaviour, challenging deterministic views of criminality. This article examines the interrelation between criminal investigations, public health, and DNA profiling, emphasizing the need for a balanced approach that maximizes benefits while mitigating risks. It concludes by advocating for policies and practices that uphold ethical standards, protect individual rights, and ensure the equitable application of DNA technologies.